FUNGSI SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN DITINJAU DARI KETENTUAN PASAL 15 UNDANG-UNDANG NOMOR 4 TAHUN 1996 - Ardani, Mira Novana (Diponegoro Private Law Review, 2017)
The granting of credit guarantees should be done directly by the grantor of the mortgage, for something because it can not be present itself, it must appoint the other party as its proxy, with SKMHT in the form of an authentic deed. This research uses empirical / sociological juridical approach. To carry out the SKMHT function, actually any credit agreement is not always made SKMHT. There are  legal consequences if after making SKMHT not followed by making APHT Keywords:  Credit, SKMHT, APHT